Check whether the following are quadratic equations:
$(2x – 1) (x – 3) = (x + 5) (x – 1)$

AcademicMathematicsNCERTClass 10

Given:

Given equation is $(2x – 1) (x – 3) = (x + 5) (x – 1)$

To do:

We have to check whether the given equation is quadratic.

Solution:

The standard form of a quadratic equation is $ax^2+bx+c=0$.

$(2x – 1) (x – 3) = (x + 5) (x – 1)$

$2x(x-3)-1(x-3)=x(x-1)+5(x-1)$

$2x^2-6x-x+3=x^2-x+5x-5$

$2x^2-x^2-7x-4x+3+5=0$

$x^2-11x+8=0$ is of the form $ax^2+bx+c=0$

Therefore, $(2x – 1) (x – 3) = (x + 5) (x – 1)$ is a quadratic equation.  

raja
Updated on 10-Oct-2022 13:20:12

Advertisements